The Family Hope Program (PKH) in Lembantongoa Village, Palolo Subdistrict, Sigi Regency from the Perspective of Effectiveness - Rahma, Rahma; Rahman, Failur; Paembonan, Laendatu; Tallesang, Mukthar; Musdayati, Musdayati (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Poverty reduction continues to be an important goal in Indonesia's plan for progress, and the Family Hope Program (PKH) was created as a way to give money to poor families in order to help improve their well-being.   This research looks at how well PKH is working in Lembantongoa Village, in Palolo Subdistrict, Sigi Regency, where the program has been in place since 2016. This type of research is descriptive qualitative research. The informants for this research are PKH Companions and PKH Recipients. Data was obtained through observation, interviews and documentation. PKH financial assistance in Lembantongoa Village is sufficient to help the economy of the Poor Households (RTM) in the areas of health for pregnant women and toddlers as well as children's basic education, in accordance with the objectives of implementing PKH. From the results of the research that researchers have conducted in the field, it shows that the stages of achieving the objectives of implementing PKH have been carried out well and are in accordance with the objectives and also the implementation of the PKH Family Hope Program (PKH) in Lembantongoa Village has improved the welfare of PKH beneficiaries.